PERSONAL COMMUNICATIVE CHARACTERISTICS OF CHILDREN OF JUNIOR SCHOOL AGE - Soliyeva Dilnozakhon Abdashimovna (Scholar Express Journal, 2023)
Learning the personal communicative characteristics of children of primary school age, The process of studying the personal communicative characteristics of children of primary school age
Keywords: Communication; communicative; cognitive